Implementasi Pendidikan Seksual pada Santri Pondok Pesantren MA Ma’ahid Kudus - Inayati, Fauziah; Rochim Maksum, Muh. Nur; Mustofa, Triono Ali; Rafsanjani, Toni Ardi (MODELING: Jurnal Program Studi PGMI, 2023)
Sexual education in Islamic boarding schools has an important role in shaping the social life of students and protecting them from the risk of sexual violence. However, with the times and needs, there is a need for a more assertive sexual education system, so that the students want to obey the rules. This study aims to identify the implementation of sexual education in the MA Ma'ahid Kudus Islamic boarding school. The research involved respondents and relevant sources and then analyzed sex education at the MA Ma'ahid Kudus Islamic boarding school. This research invites parents, surrounding people, and asatidz to care about sexual education for students so that students can be guided and stay on the right path, and can respond so that sexual harassment does not occur.